(untitled) (XXI Century. Spanish Literature and Culture, 2016)
Playwright Jordi Galceran stands out not only for being successful at the box office, but also for his literary quality. In this analysis of three plays, namely Burundanga, The Credit and The Grönholm Method, the focus is set on social satire, humour strategies and how the power structures are deconstructed in the role reversal undertaken by manipulative characters. The aim of this analysis is to try to get further information on Galceran’s perspective on 21st century reality and to distinguish the borders between comercial and literary merit theatre.